(untitled) (Global Journal of Human-Social Science, 2021)
In Joe Biden’s inauguration speech we can find standard emotional and rational stratagems that form its persuasive strategy to obtain the public’s approval. The techniques and themes used by the President are the same identified in the modern principles of commercial advertising, of the persuasion theory and of the propaganda discourses, in particular from war propaganda. These techniques and themes consist in revealing a problem in order to suggest the solution, the repetition and the simplicity of the message, the use of a colloquial language and of significant and easily understandable symbols, the participation or the quote of testimonials, the bandwagon effect, the necessity of provoking emotional responses, the plain folks appeal, the card-stacking and the use of glittering words. The attention to the choice of the most persuasive words to express the author’s ideas, to defend an ideal and to restore American identity is impressive. These stereotyped formulas are also used to simplify situations with no need of argumentation.